An Analysis of Floating Maxim in “It Ends With Us” Movie: Qualitative Research - Wildaniyah, Tazkiyatul; Mu'ammalatun, Astuti; Putri, Siti Novia Ade; Daulay, Irma Khoirot; Toyyibah, Toyyibah (Prominent, 2025)
An adaptation of Colleen Hoover's novel, "It Ends with Us" centers on domestic violence and the characters Ryle Kincaid and Lily Bloom. Considering the increasing prevalence of domestic violence in society, this research intends to examine how the film violates the maxims of the cooperative principle by using qualitative research techniques to determine the most frequent violations. The data in this analysis comes from dialogue that occurs between characters, which includes interactions that contain violations of maxims, such as the maxims of quantity, quality, relevance, and manner. The data for this study are gathered and analyzed using a qualitative descriptive method. The study examines flouting maxim in a movie using Grice's (1975) approach. It demonstrates how character routinely break the rule of relations by talking about unrelated subjects. Additionally, the maxim of manner is regularly broken, frequently in tandem with maxim of relation. There are 28 findings of flouting the quality maxim and 18 data of violating the quantity maxim.